Enhancing healthcare quality and outcomes for peritoneal dialysis patients in Thailand: An evaluation of key performance indicators and PDOPPS cohort representativeness - Boongird S. (2023)
AIM: To assess whether the peritoneal dialysis (PD) centres included in the Peritoneal Dialysis Outcomes and Practise Patterns Study (PDOPPS) in Thailand are representative of other PD centres in the country, based on 8 key performance indicators (KPIs 1-8). METHODS: A retrospective analysis was conducted comparing PD-related clinical outcomes between PD centres included in the PDOPPS (the PDOPPS group) and those not included (the non-PDOPPS group) from January 2018 to December 2019. Logistic regression analysis was used to identify predictors associated with achieving the target KPIs. RESULTS: Of 181 PD centres, 22 (12%) were included in the PDOPPS. PD centres in the PDOPPS group were larger and tended to serve more PD patients than those in the non-PDOPPS group. However, the process and outcome KPIs (KPIs 1-8) were comparable between the 2 groups. Large hospitals (≥120 beds), providing care to ≥100 PD cases and having experience for >10 years were independent predictors of achieving the peritonitis rate target of <0.5 episodes/year. Most PD centres in Thailand showed weaknesses in off-target haemoglobin levels and culture-negative peritonitis rate. CONCLUSIONS: The PD centres included in Thai PDOPPS were found to be representative of other PD centres in Thailand in terms of clinical outcomes. Thus, Thai PDOPPS findings may apply to the broader PD population in Thailand.